Biodiversity and adaptive strategy to Antarctica: the tardigrades - VECCHI, MATTEO; GIOVANNINI, ILARIA; ALTIERO, Tiziana; REBECCHI, Lorena; BERTOLANI, Roberto; GUIDETTI, Roberto; Mcinnes, Michele Cesari Sandra (Università di Ferrara, 2014)
Tardigrades are important members of the Antarctic biota in terms of abundance, distribution, and colonized substrates. Despite their importance and regular occurrence in the harsh Antarctic terrestrial ecosystems, there have been few ecological or taxonomic studies. We carried out an extensive sampling campaign along Victoria Land coastal line, collecting 180+ samples of lichens, mosses and freshwater sediments over a c. 600 km North–South transect. These samples revealed an unexpectedly high diversity: 14 species, four of which new for science. Our results have underlined the level of undiscovered biodiversity in Antarctica. Some species had very localized distribution and occurred in specific substrates (e.g. moss or lichen). Other species were more scattered, and one (the endemic Acutuncus antarcticus) was present in almost all sampling areas and substrate types. This situation indicates that, as in temperate areas, Antarctica has tardigrade species with low dispersal capabilities, and a few species with high dispersal capabilities. Surprisingly, the genetic variability of A. antarcticus (COI gene) was extremely low even between very distant populations. Laboratory experiments on the adaptive strategy of A. antarcticus indicated a very short life cycle (c. 3-4 months), shorter than in species from temperate regions. Moreover, A. antarcticus exhibits thelytoky and has cryptobiotic capabilities. These attributes allowed this species to colonize almost all viable habitats in Antarctica